A FRAMEWORK FOR PROGRESS MEASUREMENT BASED ON INTEGRATED MONITORING OF PREREQUISITES AND WORK PERFORMANCE - Marinković, Dejan; Ivanović, Marija; Simić, Nevena; Knežević, Nikola (Journal of Applied Engineering Science, 2024)
The successful implementation of construction projects necessitates the establishment of an efficient system for project execution planning and control, with parameters that ensure an effective assessment of the construction work status, timely detection of variance causes, and reliable trend analysis. In this regard, a set of parameters has been developed, among which the actual progress of works on a project holds a significant place. Existing approaches to progress measurement is mostly focused on studying methods for calculating the percentage of completed works and their applicability to specific types of works and organizational levels. However, key issues persist, such as delayed identification of variance causes and inadequate method sensitivity to initial variances when damages are still minor, and potential effects of corrective measures are greatest. Therefore, this paper proposes a framework for progress measurement based on integrated monitoring of prerequisites for tasks and work performances. While progress monitoring at the project level is organized within workflows, monitoring within each workflow is provided for sub-workflows related to ensuring prerequisites, material procurement, and construction work execution. Visualization of sub-workflows is facilitated through planned and actual cumulative curves of completed works in percentage, whose interrelationships promptly indicate potential project issues. The application of the proposed framework ensures better synchronization of construction works, improved control of prerequisites, rapid detection of causes, along with efficient variance management. The framework includes a clear division of responsibilities for implementing sub-workflows, where site management and specialized services of a company are responsible for ensuring prerequisites and material procurement, while production forces of a company primarily handle the execution of construction works. Such an approach allows for direct determination of issues or quick and efficient delineation of responsibilities, which represents a common issue in practice. This contributes to the motivation of employees and enhances the performance of the project management team.